2018 15th International Conference on the European Energy Market (EEM) 2018
DOI: 10.1109/eem.2018.8470023
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Non-Zero Price Bids for EVs in Energy and Reserves Markets Using Stochastic Optimization

Abstract: In power systems, demand and supply always have to be balanced. This is becoming more challenging due to the sustained penetration of renewable energy sources and their inherit uncertain production. Because of the increasing amount of electrical vehicles (EVs), and the high capacity and flexibility of their charging process, EVs are a good candidate for providing balancing services to electric systems. We propose a stochastic optimization method for an EV aggregator that models the uncertainty of the imbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The simulation then proceeds step by step through every time step, providing the solution method with updated information from the data provider and receiving new decisions from the solution method as illustrated in Figure 1. For a mathematical formulation of the complete problem, see [36].…”
Section: Solution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation then proceeds step by step through every time step, providing the solution method with updated information from the data provider and receiving new decisions from the solution method as illustrated in Figure 1. For a mathematical formulation of the complete problem, see [36].…”
Section: Solution Methodsmentioning
confidence: 99%
“…A two stage stochastic optimization model (SO2) that uses binary variables to determine whether a price bid will be accepted or not. It was originally developed by Van der Linden et al [36] and improved by making the MIP formulation more tight and compact, as presented in the work where this model is used for dealing with market participation constraints [24].…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to take into account a maximum and minimum quantity (Q max , Q min ) to either increase or decrease energy of EVs because the price and quantity relationship can provoke negative utilities for the CS if not managed appropriately. Thus, these bid quantities are calculated from (7), assuming there aren't any utilities obtained from buying or selling electricity to EVs, the utilities are instead obtained from balancing services offered to the grid. These maximum and minimum quantities limit the bid to provide balancing services when controlling an energy increase bid (+Qbid) in ( 8) and an energy decrease bid (−Qbid) in (9).…”
Section: A Pricing Modulementioning
confidence: 99%
“…They considered additional penalties to customers and to the energy aggregator, in case of energy variations from the day ahead. Likewise, van der Linden et al [7] showed a bidding strategy and control over bid pricing that works when the energy price is lower than the market capacity clearing price. Chen et al [8] proposed an energy management system with V2G capability and a photovoltaic (PV) CS where EVs are classified in rigid and flexible loads to support ancillary services.…”
Section: Introductionmentioning
confidence: 99%